The effect of job displacement on couples' fertility decisions - Kristiina Huttunen; Jenni Kellokumpu (Institute for the Study of Labor (IZA), 2012)
This paper analyzes the effects of job displacement on fertility using Finnish longitudinal employer-employee data (FLEED) matched to birth records. We distinguish between male and female job losses. We focus on couples where one spouse has lost his/her job due to a plant closure or mass layoff and follow them for several years both before and following the job loss. As a comparison group we use similar couples that were not affected by job displacement. In order to examine the possible channels through which job loss affects fertility we examine also the effect on earnings, employment and divorce. The results show that woman's own job loss decreases fertility mainly for highly educated women. For every 100 displaced females there are approximately 4 less children born. Male job loss has no significant impact on completed fertility.
Keywords: J65; J13; J12; 330; plant closure; employment; earnings; divorce; fertility; Kündigung; Geschlecht; Qualifikation; Fruchtbarkeit; Scheidung; Finnland